Development Of Mathematics Learning Module Using Inquiry Method Based On Etnomatematics - Tanjung, Ikke Maldina (Yana Research, 2022)
This study aims to develop a product in the form of a Mathematics Learning Module with the step of completion of the Inquiry Method and associated with Ethno in North Sumatra, especially Medan, researchers raised buildings in North Sumatra, namely the Grand Mosque and Maimun Palace. The teaching material presented by the researcher is Trigonometry for class XI MA/SMA students. The subjects in this study were students of class XI• MIA 2 MAN 1 Medan. The procedure for developing the mathematics learning module in this study refers to the 4D development model which is modified to become 3D, namely: the definition stage (define), the planning stage (design), and the development stage (develop). The instruments used in this research are validation sheets to measure the validity of the developed learning modules, learning implementation assessment sheets and student response questionnaires as well as learning outcomes tests to measure the effectiveness of the learning modules. The learning module developed in this study was declared valid, based on the average module validation score of 4.65 which met the very good category, the teacher's assessment of the module was 4.6 in the very good category, and student responses in the very good category. This learning module has met the effective criteria based on the percentage of classical learning completeness of 83.3%